Antimicrobial Resistance Patterns of Extended Spectrum Β-Lactamase Producing Klebsiellae and E. coli Isolates from a Tertiary Hospital in Ghana - P.K., Feglo; Y., Adu-Sarkodie (European Scientific Journal, ESJ, 2016)
Introduction: High proportions of E. coli and Klebsiellae isolates at Komfo Anokye Teaching Hospital (KATH) have developed resistance to the commonly prescribed antimicrobial drugs, but the cause of which is unknown. Detailed data upon which to advocate control interventions are scanty. This study determined the prevalence of ESBL Klebsiellae and E. coli at KATH, so as to establish the linkage (if any) between ESBL production and drug resistance to antimicrobials drugs at the Komfo Anokye Teaching Hospital. Method: 405 isolates consisting of 156 E. coli strains and 234 Klebsiella pneimoniae and 15 Klebsiella oxytoca were collected and tested for their antimicrobial susceptibility, ESBL production and the ESBL genotypes were determined by PCR. Results: High proportions of isolates were resistant to the β-lactam antibiotics with ampicillin recordeing 391 (91.7%) resistance followed by cefpodoxime 299 (73.8%), cefuroxime 286 (70.6%), ceftriaxone 224 (55.3%) and then cefotaxime 195 (48.1%). Proportion of isolates resistant non β-lactams tested ranged from 61% - 79%. ESBL producers had higher resistance proportions than non-ESBL producers. ESBL prevalence range from 49.4% in E coli, 61.5% in Klebsiella kpeumoniae to 86.7% in Klebsiella oxytoca. ESBL genotypes TEM, CTX-M were found in 151(64.5) isolates while 70(29.9) acquired the three ESBL genotypes. Conclusion: The widespread prevalence of ESBL producing E. coli and Klebsiellae call for immediate intervention strategies to prevent further spread. Training of laboratory personnel on phenotypic testing of ESBLs in addition to training clinical staff and prescribers on ESBL issues are advocated.